Synthesis and Study of Click-Crosslinked Polyanionic Hydrogel Networks - Stewart, Sarah Alison (My University, 2018)
Cell encapsulation aims to treat a variety of hormone- and enzyme-deficiency disorders by immobilizing therapeutic cells within a semi-permeable protective membrane. The membrane allows for in-diffusion of oxygen and nutrients and out-diffusion of waste and therapeutic proteins while simultaneously providing protection from immune cells and antibodies. Many cell therapies aim to provide long-term treatment for diseases, and designing materials that can match the longevity is critical. Synthetic polymers offer an attractive route to long-term encapsulation due to their tunable degradability and the ease of incorporating reactive moieties for covalent crosslinking. The primary goal of the work presented in this thesis was the development of non-degradable covalently crosslinked hydrogels formed by mutually reactive polymers for use as cell immobilizing platforms. Due to research showing that polycations incite immune responses in vivo this project aimed to avoid the use of polycations entirely. The covalent crosslinking occurs in the presence of cells, making it essential to select reactions that do not require toxic catalysts or form offensive by-products. Diels-Alder and thiol-ene Michael Addition click reactions were chosen due to their proven cytocompatibility and modular nature. In chapters 2 and 3, poly(methyl vinyl ether-alt-maleic anhydride) (PMMAn) was functionalized with furfurylamine (FFA) and N-2-(aminoethyl)maleimide (MAL) to form PMM-FFA and PMM-MAL, Diels-Alder reactive furan- and maleimide-bearing pendant polymers. Aqueous solutions of the polymers form bulk gels at higher concentrations (>5% w/v) and the chemical and physical properties of the gels were investigated and found to be highly tunable, with promise for use in controlled drug delivery applications. Alginate-templated matrix beads were also prepared at significantly lower polymer loading percentages (0.5 – 1.5% w/v each) and at physiological pH, and properties such as swellability and permeability were explored. This work demonstrates the first use of Diels-Alder crosslinking to reinforce alginate beads, and the matrix beads were found to have good initial cell viability post-encapsulation with 3T3 cells. In chapter 4, PMMAn was functionalized with cysteamine vinyl sulfone (CVS) to form PMM-CVS, a vinyl sulfone-bearing pendant polymer, and aqueous solutions were mixed with equimolar PEG-dithiol to form bulk hydrogels at concentrations between 2.5 and 7.5% w/v PMM-CVS. Thiol-ene crosslinking allowed for much more rapid gelation compared to the Diels-Alder system. Physical and chemical properties of the gels were explored, and excellent cytocompatibility of the crosslinking reaction was demonstrated. The ability to rapidly post-functionalize the gels in a step-wise fashion offers a versatile route to post-modification with various molecules. In chapter 5, PMMAn was functionalized with 2-pyridylthio cysteamine (SPy) to form PMM-SPy, a protected thiol. Alginate-templated matrix beads containing PMM-CVS and PMM-SPy were treated with TCEP to deprotect the thiol, allowing covalent crosslinking to occur in a controlled manner. Physical and chemical properties of the beads were explored in detail and the system was found to be highly tunable.
Keywords: hydrogels; polymers